2022
DOI: 10.35516/jmj.v56i1.219
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Positive Bacterial Infections and Antibiotics Resistance in Jordan: Current Status and Future Perspective

Abstract: Background: Antibiotic resistance is expanding worldwide at alarming rates. Middle East countries including Jordan have high prevalence of antibiotic resistance. Aims: The main aims of this review are to summarize the situation with Gram-positive bacterial infections and antibiotic resistance in Jordan, identify areas where further investigation is required, and suggest strategies to combat antibiotic resistance. Methods: A systematic literature search was conducted by two independent researchers u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…According to clinical indications, antifungal drugs are classified into two groups, the first group is antifungals for systemic infections, including: amphotericin B (1), flucytosine (2), ketoconazole (3), fluconazole (4), miconazole (5) 6), 27 the structure of the compounds are as shown in Figure 1. The second group of antifungals for dermatophyte and mucocutaneous infections includes griseofulvin (7), clotrimazole (8), econazole (9), isoconazole (10), tioconazole (11), bifonazole (12), nystatin (13), tolnaftate (14) and other topical antifungals candicidin (15), undecylenic acid (16) and natamycin (17), 37 the structure of the compounds is shown in Figures 2-3.…”
Section: Anti-fungalmentioning
confidence: 99%
See 1 more Smart Citation
“…According to clinical indications, antifungal drugs are classified into two groups, the first group is antifungals for systemic infections, including: amphotericin B (1), flucytosine (2), ketoconazole (3), fluconazole (4), miconazole (5) 6), 27 the structure of the compounds are as shown in Figure 1. The second group of antifungals for dermatophyte and mucocutaneous infections includes griseofulvin (7), clotrimazole (8), econazole (9), isoconazole (10), tioconazole (11), bifonazole (12), nystatin (13), tolnaftate (14) and other topical antifungals candicidin (15), undecylenic acid (16) and natamycin (17), 37 the structure of the compounds is shown in Figures 2-3.…”
Section: Anti-fungalmentioning
confidence: 99%
“…However, the use of synthetic anti-infectives has been reported to cause side effects and resistance, such as resistance to the antibiotics ampicillin, amoxicillin, penicillin, cefotaxime, cefazolin, methicillin, erythromycin, lincomycin, clindamycin and vancomycin against S. mutans, with the greatest resistance in 87 adults being to amoxicillin (14.8%) and lincomycin (28.7%), and the greatest resistance in 87 children being to penicillin (27.6%) and vancomycin (42.5%). [7][8][9] With regard to the resistance of several antifungal agents to C. albicans, it has been reported that C. albicans has a relatively high level of resistance to several antifungal agents, such as nystatin, fluconazole, flucytosine and echinocandin. [10][11][12][13] The ongoing development of anti-infective drugs underscores the paramount importance of efficacy and safety in identifying compounds with no adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Despite enhanced preventive measures and surveillance, MRSA remains an enduring challenge in Jordanian healthcare settings. Limited published reports exist to unveil the genotypes of MRSA in Jordan, indicating a significant gap in our understanding of the specific genetic characteristics of circulating strains [6][7][8][9][10][11][12][13][14][15][16][17]. Alzoubi et al (2014) investigated 210 nasal swabs from children aged 6-11 years and predominantly identified SCCmec type IV, with t223 as the primary spa type [18].…”
Section: Introductionmentioning
confidence: 99%